Being a parent in the field: implications and challenges of accompanied fieldwork - Braukmann, Fabienne; Haug, Michaela; Metzmacher, Katja; Stolz, Rosalie (Culture and social practice, 2020)
Frontmatter -- Contents -- Acknowledgements -- On Being a Parent in the Field -- Rethinking the Ethnographer -- Unexpected Resonances -- Circulating Family Images -- Returning to the Field as a Mother -- Entangled Family -- Falling in and out of Sync in Upland Laos -- “We Will Go on Vacation, while You Work” -- Bringing My Wife and Children to the Field -- On Being a Father in the Field -- Whisky, Kids and Sleepless Nights -- Capturing Sounds -- Shared Field, Divided Field -- From Tightrope Walks to Entangled Families -- Authors